The Role of Regions in EU-China Relations - Tomasz Kamiński (Łódź University Press, 2021)
More and more regions are cooperating with their Chinese counterparts in many different areas: economy, environment, culture, academic exchange. Although the subnational dimension has started to be a visibly important element of EU-China relations, this trend is not reflected in the academic literature on EU-China relations. Until now, we have not known what the network of contacts with China at the regional level looks like and what the determinants and institutional forms of inter-regional partnerships there are. The present book maps Sino-European relations at the regional level and presents a detailed analysis of subnational contacts in the six analysed EU member states, illustrated by case studies of interesting regions from each country. It shows the rising role of non-state actors in international relations, the growing importance of paradiplomacy, as well as the necessity to look at the EU-China relations as a multi-layer phenomenon, engaging different types of actors on different levels.